Analisis Penilaian Kepuasan Pasien Rawat Jalan Terhadap Kualitas Pelayanan Laboratorium RSUD Dr. Slamet Garut - Gina Nafsa Mutmaina (STIKes Karsa Husada Garut, 2014)
Service quality related with patient satisfaction. Patient satisfaction is an individual thing, every patient will have different levels of satisfaction depend on their respective backgrounds. Patient satisfaction is one of the health service quality measurement which is useful for input in planning, actuating and controlling the management of health service. The purpose of this study was to determine the factors that influence patient satisfaction on service quality in the laboratory of dr. Slamet Garut in 2013. This research is a descriptive analytic study with cross-sectional study design. The population in this study were 100 patients from laboratory patient of dr. Slamet Garut. Data analysis techniques using statistical Chi Square test. Based on the results of this study concluded that the factors that influence patient satisfaction are convenience laboratory, relationships between laboratory personnel with patients, laboratory personnel competence and laboratory costs. Convenience laboratory is the most dominant variable in affecting patient satisfaction toward the service quality of laboratory dr. Slamet Garut in 2013. Laboratory dr. Slamet Garut has a good service quality, seen from the high level of patient satisfaction toward the service quality of laboratory dr. Slamet Garut high. From the 100 respondents, 90% satisfied, 9% very satisfied and 1% are not satisfied for all dimensions of service care. Because most of the characteristics of the respondents have the same background. Suggest to do research with the variety characteristic respondents.